The effects of clown intervention on worries and emotional responses in children undergoing surgery - Fernandes, Sara (2010)
Submitted by Patrícia Paula Ferreira (patricia.arriaga@iscte.pt) on 2010-11-01T04:00:24Z No. of bitstreams: 1 2010_Journal_Health_Psychology.pdf: 228937 bytes, checksum: 456ebe7bed9ebc7a40224564e912c90f (MD5)